Qatar : 2009 Article IV Consultation-Staff Report; and Public Information Notice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
TheastaffareportaforaQatar'sa2009aArticleaIVaConsultation describes economic development and policies. The underlying strength of the economy derivedafrom aQatar'sahydrocarbona revenues, and timely and decisive intervention by the government in the banking system has helped to limit the impact of the global crisis and maintain financial stability. Aacornerstonea ofaQatar'sastrategyaisa commitment to diversify the economy by building related industries around the full liquefied natural gas value-chain and linking upstream, midstream, and downstream components.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet